Access to Healthy Built and Natural Environments and Physical Activity and Screen Time in New Zealand Adolescents: A Geospatial Cross‐Sectional Study - L. Marek; J. Wiki; S. Mandic; J. C. Spence; M. Smith; E. García Bengoechea; K. J. Coppell; S. Kingham; M. Hobbs (GeoHealth)
Abstract The built and natural environment can facilitate (un)healthy behaviors in adolescence. However, most previous studies have focused on examining associations between singular aspects of the environment. This study examined the association between the mixture of health‐promoting and health‐constraining environmental features in a Healthy Location Index (HLI) and physical activity and screen time among adolescents. This cross‐sectional study used data from the Built Environment and Active Transport to School (BEATS) Research Program based in Dunedin, New Zealand. Data from 1,162 adolescents with complete demographic, health behavior and spatial records were included in the analysis. The environment was defined using the HLI based on access to health‐promoting (e.g., greenspace, blue space, physical activity facility) and health‐constraining (e.g., fast‐food outlets) features and their mixture. Quantile g‐computation and multilevel mixed effects models, with adolescents nested within schools, examined associations between the environment and the two health behaviors. A positive association existed between meeting physical activity guidelines and access to health‐promoting environments (OR = 1.23 [95% CI 1.03; 1.47]), particularly blue space. In addition, the mixture of health‐promoting and health‐constraining environments was also important (ψ = 1.18 [1.01; 1.37]). However, there was limited evidence of an association between the environment and screen time. We provide evidence of a relationship between health‐promoting environments, the mix of health‐promoting and health‐constraining environments, and physical activity among adolescents. The findings support the hypothesis that the environment has the potential to positively influence healthy behaviors of youth, particularly when it comes to physical activity.